Meditation for Depression A Systematic Review of Mindfulness-Based Cognitive Therapy for Major Depressive Disorder - Sorbero, Melony E. (RAND Corporation, 2015)
RAND researchers conducted a systematic review that synthesized evidence from randomized controlled trials of mindfulness-based cognitive therapy-used adjunctively or as monotherapy-to assess its efficacy and safety in treating adults with major depressive disorder.